Attention-deficit hyperactivity disorder and impulsivity in female patients with fibromyalgia - Yılmaz, Ertan (Neuropsychiatr Dis Treat, 2018)
OBJECTIVE: Data which indicate a greater role of the central nervous system in the etiology of fibromyalgia are increasing. The goal of the present study is to determine the link between fibromyalgia and attention-deficit hyperactivity disorder (ADHD) and, in addition, to reveal the relevance of impulsivity dimension. METHODS: The study included 78 females with fibromyalgia who applied to a physical medicine and rehabilitation polyclinic in Ceyhan State Hospital and 54 healthy females. The diagnosis of fibromyalgia was made by an experienced specialist of physical medicine and rehabilitation based on the American Rheumatology Association Diagnostic Criteria (2010). The diagnosis of ADHD was by an experienced psychiatrist using Diagnostic and Statistical Manual of Mental Disorders-5. The following inventories were used: adult ADHD self-report scale, Wender Utah rating scale, and Barratt impulsivity scale short form. RESULTS: Adult ADHD was detected in 29.5% of the fibromyalgia group and 7.4% of the control group; childhood and adolescent attention hyperactivity disorder ratios in these groups were 33.3% and 11.1%, respectively. The differences were statistically significant (P=0.002, P=0.003). Scores of the fibromyalgia group on the Wender Utah rating scale, adult ADHD self-report scale, attention subscale, hyperactivity–impulsivity subscale, and the Barratt impulsivity scale for non-planning and attentional impulsivity were found to be significantly higher than the control group (P<0.05, P<0.01, P<0.01, P<0.05, P<0.01, P<0.05, respectively). CONCLUSION: The present study has shown that both adult and childhood ADHD are quite common in female fibromyalgia patients. There was a link between fibromyalgia and impulsivity. Certain subtypes of fibromyalgia and attention-deficit hyperactivity deficit disorder could be sharing the common etiological pathways.